Laparoscopic Versus Open Partial Nephrectomy: A Systemic Review and Meta-Analysis of Surgical, Oncological, and Functional Outcomes - You, Chengyu; Du, Yuelin; Wang, Hui; Peng, Lei; Wei, Tangqiang; Zhang, Xiaojun; Li, Xianhui; Wang, Anguo (Frontiers in Oncology, 2020)
Purpose: To summarize and analyze the current evidence about surgical, oncological, and functional outcomes between the LPN and OPN. Materials and Methods: Through a systematical search of multiple scientific databases in March 2020, we performed a systematic review and cumulative meta-analysis. Meanwhile, we assessed the quality of the relevant evidence according to the framework in the Cochrane Handbook for Systematic Reviews of Interventions. Results: A total of 26 studies with 8095 patients were included. There was no statistical difference between the LPN and OPN in the terms of operation time(p=0.13), intraoperative complications(p=0.94), recurrence (p=0.56), cancer specific survival(p=0.72), disease free survival (p=0.72) and variations of estimated glomerular filtration rate(p=0.31). The LPN group had a significantly less estimated blood loss (P<0.00001), lower blood transfusion(p=0.04), shorter length of hospital stay(p<0.00001), lower total complications(p=0.03) and postoperative complications(p=0.02), higher positive surgical margin(p=0.005), higher overall survival((p<0.00001),and less increased serum creatinine(p=0.002).The subgroup analysis showed that no clinically meaningful differences were found for T1a tumors in terms of operation time(p=0.11),and positive surgical margin(p=0.23). In addition, the subgroup analysis also suggested that less estimated blood loss(p<0.0001) and shorter length of hospital stay(p<0.00001) were associated with the LPN group for T1a tumors. Conclusions: This meta-analysis revealed that the LPN is a feasible and safe alternative to the OPN, with comparable surgical, oncologic and functional outcomes. However, the results should be applied prudently in clinic because of the low quality of evidence. Further quality studies are needed to evaluate effectiveness LPN and its postoperative quality of life compared with OPN.